Tapping into the Power of Sol-Gel Method for Enhanced Antimicrobial Activity of Titania Nanoparticles - Saputra, Kormil; Masruroh, Masruroh; Susanto, Hendra; Apsari, Retna (Science and Technology Indonesia, 2024)
Increasing bacterial resistance to antibiotics has become a serious threat to global public health. In this context, this study aims to evaluate the antimicrobial activity of titanium dioxide nanoparticles (TiO2 NPS) synthesized using the sol-gel method. TiO2 NPS samples were prepared and characterized for morphology via field-emission scanning electron microscopy (FESEM) and X-ray diffraction (XRD) analysis. Kirby-Bauer disc diffusion method was used to test the antimicrobial activity of TiO2 NPS against Gram positive bacteria Staphylococcus aureus, Gram negative bacteria Escherichia coli, and pathogenic fungus Aspergillus penicillioides. The results showed that TiO2 NPS effectively inhibited the growth of microorganisms, with significant inhibition zones especially against fungi. The antimicrobial mechanism of TiO2 NPS involves the formation of hydroxyl radicals and superoxide ions that damage the cell membrane of microorganisms. The implications of this study are the development of potential antimicrobial nanomaterials for biomedical and environmental applications, as well as the importance of considering the physical and chemical properties of TiO2 NPS in designing effective infection treatment strategies.